2017
DOI: 10.1021/acs.jpcc.6b12943
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Stabilization of Metastable TiO2 Films

Abstract: This work demonstrates a phenomenon that preserves the traditionally metastable anatase crystal structure of thin titania (TiO2) films along a two-dimensional oxide interface at temperatures well in excess of those that normally trigger a full polymorphic transformation to rutile in higher dimensionality crystalline powders. Whereas atomic surface mobility appears to dominate polymorph transformation processes within bulk TiO2 powders, a simple reduction in dimen-sionality to a two-dimensional TiO2 film (ca. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Indeed, the wetting of isolated crystallites by SiO2 thin films also appears to enhance the interfacial stabilization of anatase crystallites. Increased loading of TiO2 crystallites closely adhered to the SiO2 surface probably also leads to a degree of confinement-based stabilization as we have reported recently, 57 consistent with the apparent interfacemediated stabilization observed even for nonsiliceous templates (e.g., styrene 20 ) as discussed earlier.…”
Section: 31 − 3346supporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the wetting of isolated crystallites by SiO2 thin films also appears to enhance the interfacial stabilization of anatase crystallites. Increased loading of TiO2 crystallites closely adhered to the SiO2 surface probably also leads to a degree of confinement-based stabilization as we have reported recently, 57 consistent with the apparent interfacemediated stabilization observed even for nonsiliceous templates (e.g., styrene 20 ) as discussed earlier.…”
Section: 31 − 3346supporting
confidence: 90%
“…This concept is derived from our recent report of anatase stabilization along the interface of thin TiO2 films deposited on oxide support layers (i.e., TiO2/SiO2). 57 Specifically, we have shown that the anatase polymorph can be stabilized by the TiO2-SiO2 interface at temperatures well in excess of the characteristic Huẗtig temperature identified for bulk TiO2. This results from the apparent interface-mediated mitigation of atomic surface mobility that typically favors the polymorphic transformation from anatase to rutile in bulk powders.…”
Section: 31 − 3346mentioning
confidence: 80%
“…PEDOT: PSS (PH 1000) was purchased from Ossila Ltd.(Sheffield, UK). TiO 2 sol-gel was prepared by following the procedure reported by Gregory et al [51]. Anhydrous sodium sulfate and potassium carbonate were purchased from Thermo Fisher Scientific (Thailand) Ltd. (Bangkok, Thailand).…”
Section: Methodsmentioning
confidence: 99%
“…During the synthesis, 2.7 mL titanium (IV) butoxide (97%, Sigma Aldrich, MO, USA), 0.57 mL ethyl acetoacetate (99%, Sigma Aldrich), 57 μL 2,4-pentanedione (99%, Sigma Aldrich, MO, USA) and 57 μL 2,3-butanedione (97%, Sigma Aldrich, MO, USA) were mixed and stirred at room temperature overnight [37].…”
Section: Methodsmentioning
confidence: 99%